Numerical modeling of masonry vaults strengthened with transversal diaphragms - Ptaszkowska, Joanna (2014)
Masonry vaults and arches are one of main structural elements present in most of historical constructions. Due to the impact of time, load and other construction features, their strength capacity decreases making them more vulnerable to failure. That is why, to maintain the role of the vaults and arches and prevent them from failure, strengthening is needed. Dur- ing the strengthening evaluation it cannot be forgotten that historical constructions are part of cultural heritage and engineers are required to follow the conservation doctrine of mini- mum intervention, among other relevant principles. This condition involves detailed studies before proceeding with application of strengthening. Within this framework, numerical mod- eling appears as a very useful method to study and define the efficiency of potential interven- tions before its application. The main objective of this paper is the numerical study of masonry vaults strengthened by means of extrados stiffening diaphragms. The idea of transversal stiffening elements is in line with the new trend in restoration practices regarding the use of traditional material and tech- niques while designing strengthening solutions. Preparation and validation of numerical models was done according to experiments carried out at University of Padova, Italy. Based on the experimental parameters and geometry, two numerical models, built up on macro- and micro- approaches, were constructed in DIANA Finite Element Analysis software. The pur- pose of making two models was the comparison of structural response of each one to mono- tonic, incremental load and to conclude on usefulness of macro-modeling approach for masonry arch-type constructions. Further, analysis of the efficiency of strengthening tech- niques throughout the non-linear analysis on both model types was performed. Extrados stif- fening diaphragms were defined to be a valid technique for improving the structural response of masonry arches and vaults, particularly in terms of initial stiffness.